Insulating material and preparation method and application thereof
By using core-shell quantum dot/polyethylene composite materials and crosslinking agents in high-voltage DC cables, a boundary effect is formed, which solves the problem of increased conductivity under high-temperature and strong electric fields, significantly improves insulation performance and suppresses space charge accumulation.
Patent Information
- Application Number
- CN202410268957.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-03-08
AI Technical Summary
The increased conductivity of the high-voltage DC cable insulation layer under high temperature and strong electric field leads to the inversion of the electric field and the accumulation of space charge, resulting in insulation failure.
Using core-shell quantum dot/polyethylene composite materials, an n-n-type semiconductor heterostructure is formed through the core-shell interface, limiting electron and hole migration, inhibiting space charge accumulation, and combining peroxide crosslinking agents and antioxidants to improve insulation performance .
Under high temperature and strong electric field conditions, the conductivity of insulating materials is significantly reduced, the insulation performance is improved, the space charge accumulation is reduced, and the service life of insulating materials is extended.
Smart Images

Figure CN118165392B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of insulating materials, and in particular relates to an insulating material and a preparation method and application thereof. Background Art
[0002] High-voltage direct current transmission (HVDC transmission) is an important means of offshore renewable energy grid connection, large-capacity long-distance power transmission and cross-regional power grid interconnection. As a key equipment in high-voltage direct current transmission projects, high-voltage direct current cables (HVDC cables) determine the reliability and stability of the transmission system. The insulation performance of high-voltage cables directly affects the efficiency and safety of power transmission.
[0003] Polyethylene (PE) has good electrical resistance, and after a cross-linking reaction, cross-linked polyethylene can be formed, which can further improve the heat resistance and mechanical properties. Polyethylene has become the main material for extruded insulation of high-voltage cables today. However, the electric field distribution of the insulation layer of a high-voltage DC cable is determined by the conductivity of the material. Under normal circumstances, the conductivity increases exponentially with increasing temperature, resulting in electric field reversal during normal operation of the DC cable. When the insulation is under DC stress for a long time, space charge accumulation will occur, further distorting the internal electric field of the insulation, which may lead to insulation failure. Therefore, providing a polyethylene cable insulation with lower conductivity under high temperature and strong electric field is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of this, the present invention provides an insulating material and a preparation method and application thereof. The insulating material provided by the present invention has low electrical conductivity under high temperature and strong electric field conditions, and can maintain good insulating properties under high temperature and strong electric field conditions.
[0005] In order to solve the above technical problems, the present invention provides an insulating material, comprising the following components in parts by mass:
[0006]
[0007] Preferably, the core-shell quantum dots include a core layer, a shell layer coated on the surface of the core layer, and an oil-soluble modified ligand on the surface of the shell layer;
[0008] The core layer and the shell layer are independently made of II-VI semiconductor materials;
[0009] The average particle size of the core-shell quantum dots is 2 to 20 nm.
[0010] Preferably, the core layer is cadmium selenide or zinc selenide;
[0011] The shell layer is zinc sulfide;
[0012] The oil-soluble modified ligand is octadecylamine.
[0013] Preferably, the peroxide cross-linking agent includes dicumyl peroxide or di-tert-butyl peroxycumene, and the antioxidant includes antioxidant 1076, antioxidant 1010 or antioxidant 300.
[0014] Preferably, the polyethylene is low-density polyethylene.
[0015] The present invention also provides a method for preparing the insulating material described in the above technical solution, comprising the following steps:
[0016] dissolving polyethylene in a first organic solvent to obtain a polyethylene solution;
[0017] dispersing the core-shell quantum dots in a second organic solvent to obtain a core-shell quantum dot dispersion;
[0018] The polyethylene solution and the core-shell quantum dot dispersion are mixed and then distilled to obtain a core-shell quantum dot / polyethylene composite material;
[0019] The core-shell quantum dot / polyethylene composite material, a peroxide cross-linking agent and an antioxidant are mixed and homogenized for absorption to obtain the insulating material.
[0020] Preferably, the distillation is vacuum distillation;
[0021] The vacuum degree of the reduced pressure distillation is 0.08-0.12 atm, and the temperature is 65-75°C.
[0022] Preferably, after the distillation, the process further comprises: washing the distilled solid with ethanol and vacuum drying in sequence.
[0023] Preferably, the temperature of the homogenization absorption is 68-72° C., and the time is 22-26 hours.
[0024] The present invention also provides the use of the insulating material described in the above technical solution or the insulating material prepared by the preparation method described in the above technical solution as an insulating material for high-voltage direct current transmission cables.
[0025] The present invention provides an insulating material, comprising the following components by mass: 100 parts of polyethylene, 0.01 to 1 parts of core-shell quantum dots, 0.5 to 2 parts of peroxide crosslinking agent and 0.5 to 2 parts of antioxidant. In the present invention, the contact interface formed by the core layer and the shell layer of the core-shell quantum dots belongs to the nn-type semiconductor heterostructure contact, the band structure of the core layer is bent downward, and the band structure of the shell layer is bent upward; the electron carriers at the bottom of the conduction band will be confined by the core-shell interface and it will be difficult to continue to migrate; the hole carriers at the top of the valence band will migrate to the shell layer due to the influence of the built-in contact potential. The core-shell interface of the core-shell quantum dots themselves provides a confining effect on the electron carriers, and the interface between the shell layer and the insulating matrix provides a confining effect on the hole carriers; and the confinement effect gradually increases with the increase in the difference in the band gap between the core layer and the shell layer of the quantum dots, thereby limiting the migration of carriers under high temperature and strong field conditions and inhibiting the accumulation of space charges, thereby improving the insulation performance of the insulating material under high temperature and strong electric field conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a dotted line graph showing the volume conductivity of the insulating materials prepared in Example 1, Example 2 and Comparative Example 1 changing with the electric field strength at 30° C.;
[0027] Figure 2 It is a dotted line graph showing the change of volume conductivity of the insulating materials prepared in Example 1, Example 2 and Comparative Example 1 with the electric field strength at 90° C.;
[0028] Figure 3 This is a comparison curve of the average space charge density of the insulating materials prepared in Example 1, Example 2 and Comparative Example 1 at a DC electric field strength of 50 kV / mm and a temperature of 25°C. DETAILED DESCRIPTION
[0029] The present invention provides an insulating material, comprising the following components in parts by mass:
[0030]
[0031] In terms of mass fraction, the insulating material provided by the present invention comprises 100 parts of polyethylene. In the present invention, the polyethylene is preferably low-density polyethylene, and the number average molecular weight of the low-density polyethylene is preferably 2×10 4 ~2×10 5 The weight average molecular weight of the low-density polyethylene is preferably 5×10 4 ~5×10 5 In the present invention, the low-density polyethylene has excellent electrical properties, good mechanical properties and good toughness, and is suitable for the production of high-voltage cables. In the present invention, the polyethylene is an insulating matrix.
[0032] Based on the mass fraction of polyethylene, the insulating material provided by the present invention includes 0.01 to 1 parts of core-shell quantum dots, preferably 0.04 to 0.06 parts. In the present invention, the core-shell quantum dots preferably include a core layer, a shell layer coated on the surface of the core layer, and an oil-soluble modified ligand on the surface of the shell layer. In the present invention, the core layer is preferably a II-VI semiconductor material, more preferably cadmium selenide (CdSe) or zinc selenide (ZnSe). In the present invention, the shell layer is preferably a II-VI semiconductor material, more preferably zinc sulfide (ZnS). In the present invention, the oil-soluble modified ligand is preferably octadecylamine. In the present invention, the average particle size of the core-shell quantum dots is preferably 2 to 20 nm, more preferably 5 to 15 nm. In the present invention, the core-shell quantum dots are uniformly dispersed in the polyethylene insulating matrix.
[0033] Based on the mass fraction of polyethylene, the insulating material provided by the present invention includes 0.5 to 2.0 parts of a peroxide crosslinking agent, preferably 1.0 to 2.0 parts. In the present invention, the peroxide crosslinking agent preferably includes dicumyl peroxide or di-tert-butyl peroxyisopropylbenzene, more preferably dicumyl peroxide.
[0034] Based on the mass fraction of polyethylene, the insulating material provided by the present invention includes 0.5 to 2.0 parts of antioxidant, preferably 1.0 to 1.5 parts. In the present invention, the antioxidant preferably includes antioxidant 1076, antioxidant 1010 or antioxidant 300, and more preferably antioxidant 1076.
[0035] The band offset of the heterogeneous interface of the core-shell nano-quantum dots in the insulating material provided by the present invention causes a sudden change in the bottom of the conduction band and the top of the valence band, which has a confining effect on electrons and holes respectively, thereby limiting the migration of carriers under high temperature and strong field and inhibiting the accumulation of space charges.
[0036] The present invention also provides a method for preparing the insulating material described in the above technical solution, comprising the following steps:
[0037] dissolving polyethylene in a first organic solvent to obtain a polyethylene solution;
[0038] dispersing the core-shell quantum dots in a second organic solvent to obtain a core-shell quantum dot dispersion;
[0039] The polyethylene solution and the core-shell quantum dot dispersion are mixed and then distilled to obtain a core-shell quantum dot / polyethylene composite material;
[0040] The core-shell quantum dot / polyethylene composite material, a peroxide cross-linking agent and an antioxidant are mixed and homogenized for absorption to obtain the insulating material.
[0041] The present invention dissolves polyethylene in a first organic solvent to obtain a polyethylene solution. In the present invention, the first organic solvent is preferably xylene. In the present invention, the mass ratio of the polyethylene to the first organic solvent is preferably 1:9 to 10, more preferably 1:10. The present invention has no special requirements for the dissolution, as long as it can be fully dissolved. In an embodiment of the present invention, the dissolution temperature is 80°C.
[0042] The present invention disperses the core-shell quantum dots in a second organic solvent to obtain a core-shell quantum dot dispersion. In the present invention, the second organic solvent is preferably toluene, xylene or cyclohexane, more preferably cyclohexane. In the present invention, the mass of the core-shell quantum dots and the volume ratio of the second organic solvent are preferably 1 mg: 0.8 to 1.2 mL, more preferably 1 mg: 1 mL. In the present invention, the dispersion is preferably carried out under ultrasonic conditions; the power of the ultrasound is preferably 30 to 200 W, more preferably 60 to 100 W; the ultrasound time is preferably 8 to 12 min, more preferably 10 min. In the present invention, the dispersion temperature is preferably 75 to 85 ° C, more preferably 80 ° C. The present invention preferably uses a water bath to provide the dispersion temperature.
[0043] After obtaining the polyethylene solution and the core-shell quantum dot dispersion, the present invention mixes the polyethylene solution and the core-shell quantum dot dispersion and then distills to obtain a core-shell quantum dot / polyethylene composite material. In the present invention, the distillation is preferably a vacuum distillation; the vacuum degree of the vacuum distillation is preferably 0.08 to 0.12 atm, more preferably 0.1 atm; the temperature of the vacuum distillation is preferably 65 to 75° C., more preferably 70° C. In the present invention, the distillation is preferably performed in a rotary evaporator.
[0044] In the present invention, after the distillation, it is preferred that the following steps are further performed: washing the distilled solid with ethanol and vacuum drying in sequence. In the present invention, the solid obtained after the distillation is preferably a powder. In the present invention, the ethanol is preferably anhydrous ethanol. In the present invention, the vacuum degree of the vacuum drying is preferably 0.08 to 0.12 atm, more preferably 0.1 atm; the temperature of the vacuum drying is preferably 65 to 75°C, more preferably 70°C; the time of the vacuum drying is preferably 10 to 14h, more preferably 12h. The present invention can remove the organic solvent remaining on the surface of the core-shell quantum dot / polyethylene composite material through ethanol washing and vacuum drying.
[0045] After obtaining the core-shell quantum dot / polyethylene composite material, the present invention mixes the core-shell quantum dot / polyethylene composite material, a peroxide crosslinking agent and an antioxidant for homogenized absorption to obtain the insulating material. The present invention has no special requirements for the mixing, as long as it can be mixed evenly. In the present invention, the temperature of the homogenized absorption is preferably 68 to 72°C, more preferably 70°C; the time of the homogenized absorption is preferably 22 to 26h, more preferably 24h. The present invention adopts the "post-absorption method" process to infiltrate the peroxide crosslinker and the antioxidant into the polyethylene insulation matrix in the form of liquid diffusion; the homogenized absorption method can effectively avoid the melt blending method causing the peroxide crosslinker to be subjected to high temperature, resulting in premature crosslinking reaction.
[0046] The present invention also provides the use of the insulating material described in the above technical solution or the insulating material prepared by the preparation method described in the above technical solution as an insulating material for high-voltage direct current transmission cables.
[0047] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] Cadmium selenide@zinc sulfide (CdSe@ZnS) is used as core-shell quantum dots;
[0050] Dissolve 5 g of low-density polyethylene pellets in 50 g of xylene at 80° C. to obtain a low-density polyethylene solution;
[0051] 2 mg of CdSe@ZnS was dispersed (ultrasonication at 80 °C and 60 W for 10 min) in 2 mL of cyclohexane to obtain a quantum dot dispersion;
[0052] The low-density polyethylene solution and the quantum dot dispersion were stirred at 80°C for 15 minutes and then transferred to a rotary evaporator for vacuum distillation at 70°C and 0.1atm. After the vacuum distillation was completed, anhydrous ethanol was used to wash the precipitated product; the precipitated product was vacuum dried at 70°C and 0.1atm for 12 hours to obtain a core-shell quantum dot / polyethylene composite material;
[0053] The core-shell quantum dot / polyethylene composite material, 0.1 g of diisopropylbenzene peroxide (cross-linking agent) and 0.05 g of antioxidant 1076 were mixed and homogenized and absorbed at 70° C. for 24 hours to obtain an insulating material.
[0054] Example 2
[0055] Zinc selenide@zinc sulfide (ZnSe@ZnS) is used as core-shell quantum dots;
[0056] Dissolve 5 g of low-density polyethylene pellets in 50 g of xylene at 80° C. to obtain a low-density polyethylene solution;
[0057] 2 mg ZnSe@ZnS was dispersed (ultrasonication at 80 °C and 60 W for 10 min) in 2 mL toluene to obtain a quantum dot dispersion;
[0058] The low-density polyethylene solution and the quantum dot dispersion were stirred at 80°C for 15 minutes and then transferred to a rotary evaporator for vacuum distillation at 70°C and 0.1atm. After the vacuum distillation was completed, anhydrous ethanol was used to wash the precipitated product; the precipitated product was vacuum dried at 70°C and 0.1atm for 12 hours to obtain a core-shell quantum dot / polyethylene composite material;
[0059] The core-shell quantum dot / polyethylene composite material, 0.1 g of diisopropylbenzene peroxide (cross-linking agent) and 0.05 g of antioxidant 1076 were mixed and homogenized and absorbed at 70° C. for 24 hours to obtain an insulating material.
[0060] Comparative Example 1
[0061] The insulating material was prepared according to the method of Example 2, except that quantum dots were not added; the specific preparation steps were as follows:
[0062] Dissolve 5 g of low-density polyethylene pellets in 50 g of xylene at 80° C. to obtain a low-density polyethylene solution;
[0063] The low-density polyethylene solution was stirred at 80°C for 15 minutes and then transferred to a rotary evaporator, and vacuum distilled at 70°C and 0.1atm. After the vacuum distillation was completed, the precipitated product was rinsed with anhydrous ethanol. The precipitated product was vacuum dried at 70°C and 0.1atm for 12 hours, mixed with 0.1g of diisopropyl peroxide (cross-linking agent) and 0.05g of antioxidant 1076, and then homogenized and absorbed at 70°C for 24 hours to obtain an insulating material.
[0064] The changes of volume conductivity of the insulating materials prepared in Example 1, Example 2 and Comparative Example 1 with electric field strength at 30° C. and 90° C. were tested using a three-electrode experimental system, and the results are listed in Table 1.
[0065] Table 1 Volume conductivity of Example 1, Example 2 and Comparative Example 1 at different electric field strengths
[0066]
[0067]
[0068] According to the data in Table 1, dotted line graphs of the volume conductivity of the insulating materials prepared in Example 1, Example 2 and Comparative Example 1 at 30° C. and 90° C. as a function of the electric field strength are drawn, as shown in FIG. Figures 1-2 As shown. Among them, Figure 1 It is a dot-line graph showing the volume conductivity of insulating materials at 30°C as a function of electric field strength; Figure 2 It is a dot-line graph showing the volume conductivity of the insulating material at 90°C as a function of the electric field strength.
[0069] Combining Table 1 and Figures 1-2 It can be seen that at 30°C and 90°C, the volume conductivity of the insulating materials prepared in Examples 1 and 2 is lower than that of the insulating material prepared in Comparative Example 1. Compared with Comparative Example 1, at a temperature of 90°C and an electric field strength of 52.67 kV / mm, the DC conductivity of the composite insulation in Examples 1 and 2 can be reduced by 39.2% and 47.2%, respectively. This indicates that the core-shell nano-quantum dot / polyethylene composite cable insulation proposed in the present invention has more excellent performance in terms of DC conductivity.
[0070] The space charge characteristics of the insulating materials prepared in Example 1, Example 2 and Comparative Example 1 were tested by pulsed electro-acoustic (PEA) at a DC electric field strength of 50 kV / mm and a temperature of 25°C. The results are as follows: Figure 3 Some of the results are listed in Table 2.
[0071] Table 2 Average space charge density of insulating materials prepared in Examples 1, 2 and Comparative Example 1
[0072]
[0073] Combining Table 2 and Figure 3 It can be seen that the space charge accumulation of the insulating materials prepared in Examples 1 and 2 is lower than that in Comparative Example 1, and the average space charge density after running for 30 minutes at 25°C and 50kV / mm field strength is reduced by 40.4% and 34.1% respectively compared with Comparative Example 1; this indicates that the core-shell nano-quantum dot / polyethylene composite cable insulation provided by the present invention has more excellent performance in space charge suppression.
[0074] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An insulating material, It is characterized in that The composition includes the following components in parts by weight: Polyethylene 100 parts; Core-shell quantum dots 0.01 to 1 part; Peroxide crosslinking agent 0.5-2 parts; 0.5-2 parts of antioxidant; The core-shell quantum dots include a core layer, a shell layer coated on the surface of the core layer, and an oil-soluble modified ligand on the surface of the shell layer; the core layer is cadmium selenide or zinc selenide; the shell layer is zinc sulfide; The method for preparing the insulating material comprises the following steps: dissolving polyethylene in a first organic solvent to obtain a polyethylene solution; dispersing the core-shell quantum dots in a second organic solvent to obtain a core-shell quantum dot dispersion; The polyethylene solution and the core-shell quantum dot dispersion are mixed and then distilled to obtain a core-shell quantum dot / polyethylene composite material; The core-shell quantum dot / polyethylene composite material, a peroxide cross-linking agent and an antioxidant are mixed and homogenized for absorption to obtain the insulating material.
2. The insulating material according to claim 1, It is characterized in that The average particle size of the core-shell quantum dots is 2 to 20 nm.
3. The insulating material according to claim 2, It is characterized in that The oil-soluble modified ligand is octadecylamine.
4. The insulating material according to claim 1, It is characterized in that The peroxide crosslinking agent includes dicumyl peroxide or di-tert-butyl peroxycumene, and the antioxidant includes antioxidant 1076, antioxidant 1010 or antioxidant 300.
5. The insulating material according to claim 1, It is characterized in that The polyethylene is low-density polyethylene.
6. A method for preparing the insulating material according to any one of claims 1 to 5, The following steps are involved: dissolving polyethylene in a first organic solvent to obtain a polyethylene solution; dispersing the core-shell quantum dots in a second organic solvent to obtain a core-shell quantum dot dispersion; The polyethylene solution and the core-shell quantum dot dispersion are mixed and then distilled to obtain a core-shell quantum dot / polyethylene composite material; The core-shell quantum dot / polyethylene composite material, a peroxide cross-linking agent and an antioxidant are mixed and homogenized for absorption to obtain the insulating material.
7. The preparation method according to claim 6, It is characterized in that The distillation is vacuum distillation; The vacuum degree of the reduced pressure distillation is 0.08-0.12 atm, and the temperature is 65-75°C.
8. The preparation method according to claim 6 or 7, It is characterized in that After the distillation, the method further comprises: washing the distilled solid with ethanol and vacuum drying in sequence.
9. The preparation method according to claim 6, It is characterized in that The temperature of the homogenization absorption is 68-72° C., and the time is 22-26 hours.
10. Use of the insulating material according to any one of claims 1 to 5 or the insulating material prepared by the preparation method according to any one of claims 6 to 9 as an insulating material for high-voltage direct current transmission cables.
Citation Information
Cited By
Insulation shielding material based on FLG (at) Ag-QDs core-shell structure quantum filler and preparation method thereof
CN120441950A
Insulating material, and preparation method and use thereof
US12516175B2
